Mathematical Model of Transmission Dynamic of Ebola Virus Disease - Yohanna, Samuel; Adamu, M. M; Hina, A. D; O, Okai J.; Jeremiah, Adejoh (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study investigates the impact of treatment and vaccination on the transmission dynamics of Ebola virus disease (EVD) within human populations, as well as the effects of environmental factors on vector populations. We formulated a system of ordinary differential equations (ODEs) to model these dynamics and applied the method of linearized stability analysis to solve the equations. The stability analysis revealed that the disease-free equilibrium (DFE) states of the models remain stable when certain parameters—specifically, the treatment rate in the human population and the recovery rate in the vector population—are appropriately adjusted. Numerical simulations demonstrated that achieving a disease-free equilibrium state requires simultaneous treatment and vaccination of the population. The findings highlight the necessity of integrated intervention strategies to effectively control EVD transmission, contributing valuable insights for public health policy and future research on infectious disease management.